TEMPORAL BEHAVIOUR OF MARINE LANDINGS ALONG COASTAL KARNATAKA III. CYCLICAL PATTERNS - GADAGKAR, SUDHINDRA R; SUNDARARAJ, N (Fishery Technology, 2017)
Marine landing data for Karnataka during 1956-1978 were subjected to timeseries analysis and cyclical periodicities isolated in the case of seven fisheries namely, ribbon fish (five year cycle); Caranx spp., Leiognathus spp, and mackerel (six year cycle each); the combined landings of Hernirhamphus spp. and Belone spp., ’Lesser Sardines’ and ’Other Clupeids’ (seven year cycle each). ’Total’ demonstrated an eight-year cyclical periodicity.